2012
DOI: 10.1242/jcs.092890
|View full text |Cite
|
Sign up to set email alerts
|

The in vivo function of mammalian cell and tissue polarity regulators – how to shape and maintain the epidermal barrier

Abstract: SummaryThe establishment and maintenance of cell and tissue polarity is crucial for a range of biological processes, such as oriented division, migration, adhesion and barrier function. The molecular pathways that regulate cell and tissue polarity have been extensively studied in lower organisms as well as in mammalian cell culture. By contrast, relatively little is still known about how polarization regulates the in vivo formation and homeostasis of mammalian tissues. Several recent papers have identified cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 92 publications
0
31
0
Order By: Relevance
“…Coordinated cell polarity is crucial in forming and shaping tissues (Bryant and Mostov, 2008;Niessen et al, 2012). When embedded in a laminin-rich matrix, a single Madin-Darby canine kidney (MDCK) cell gives rise to a cyst-like monolayer of epithelial cells surrounding a central lumen (McAteer et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Coordinated cell polarity is crucial in forming and shaping tissues (Bryant and Mostov, 2008;Niessen et al, 2012). When embedded in a laminin-rich matrix, a single Madin-Darby canine kidney (MDCK) cell gives rise to a cyst-like monolayer of epithelial cells surrounding a central lumen (McAteer et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Other than basement-membrane-associated proteins in basal keratinocytes or tight junction components in upper stratified keratinocytes, asymmetrically distributed apical basal polarity markers have yet to be defined in the epidermis (Niessen et al, 2012). Better described is the redistribution of proteins involved in the assembly and disassembly of focal adhesions during the acquisition of front-to-rear polarity in cultured single cells (Hamill et al, 2009;Ho and Dagnino, 2012b).…”
Section: Slco1b3 Expression Is Regulated By Type VII Collagenmentioning
confidence: 99%
“…(Munro, 2006;Goldstein and Macara, 2007), the CrumbsStardust-PATJ complex and the Scribble-Lgl-Dlg complex (Martin-Belmonte and Mostov, 2008;Martín-Belmonte et al, 2008). However, the role of these protein complexes in maintenance of stratified epithelia polarity is not clear (Muroyama and Lechler, 2012;Niessen et al, 2012) and recent work has shown that the engulfment and cell motility protein ELMO2 positively regulates front-to-rear keratinocyte polarity by forming complexes with ILK in the presence of EGF (Ho et al, 2009;Ho and Dagnino, 2012a;Ho and Dagnino, 2012b). The data presented here identify for the first time a link between ELMO2 and type VII collagen, demonstrating that, like ELMO2, type VII collagen can regulate front-to-rear polarity (Fig.…”
Section: Uv-induced Csccmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, subtle interactions between microbes and these epithelial surfaces have been shown to determine local immune reactions and disease. The barriers consists of three parts: an extensive epithelial cell surface exposed to the environment, a basement membrane that, together with various cell-junction structures, provides an extra level of separation, and a highly reactive lymphoid tissue underneath composed of antigen-presenting cells [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%